Consumer perception of insect-based foods in the community of Zhejiang University. - Joko Pilianto; Xiayu Hu; Hadiatullah Hadiatullah; Tshenolo Tsheko; Asim Munawar; A.S. Abou El-Ela; Wen-Wu Zhou; Zeng-Rong Zhu (The East Java Biological Society, 2022)
Insect foods are nutritious and acceptable for human consumption. The research was to determine the factors of motivation choices, satisfaction and food safety knowledge on insect foods consumption among Zhejiang University community. This study takes the form of a structured online questionnaire designed by the investigators for this convenience sample survey. Data were collected from Zhejiang University, China. A total of 873 respondents, (students, teachers and staff) ranging in age from 18 to 85 years (503 men and 370 women) completed the survey. Factor analysis was employed to identify related variables. An analysis revealed three factors; what motivates insect foods consumption by the respondents showed that taste (40.4%) is the major reason to consume insect foods followed by nutritional value (27.3%) and affordability (13.9%). Majority of the respondents were satisfied with the price of insect foods (51.7%). The survey also showed that majority of respondents did not have food safety concerns on the potential toxicity of insect (47.2%), 33% were concerned, while 19.8% did not think about the safety concerns. The study revealed that males between 18-28 years consume insect foods more than females in the same age group. Although some insect foods may be toxic, consumption is enjoyed by many of the respondents and they are not discouraged from consuming them. This study shows the current trend on insect foods consumption, bring awareness on the safety of insect foods consumption and promote insect foods consumption as some edible insects are reported to have health benefits.